Can vasopressin levels predict autism spectrum disorder severity? A case-control study - Mohamed Afify; Asmaa kamel; Mohamed Abdel-Hakeem; Marwa Ali (Egyptian Pediatric Association Gazette)
Abstract Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder with onset in early childhood. Its primary characteristics are impaired social communication and interaction, along with restricted and repetitive behaviors. Several studies have shown that vasopressin acts as a neuromodulator and neurotransmitter in various modes of interneuron communication. Given its influence on brain regions such as the amygdala, hippocampus, striatum, hypothalamus, and nucleus accumbens, vasopressin is thought to play a role in the social communication and repetitive behaviors observed in ASD. Objectives The aim of this study was to evaluate plasma vasopressin levels in children with ASD in relation to the severity of their autism symptoms. Methods This case-control study was conducted at the Pediatric Neuropsychiatric Clinic at Minia University Hospital over 1 year. All children included in the study underwent a comprehensive history review, thorough clinical examination, evaluation of autism symptom severity using the Gilliam Autism Rating Scale, third Edition (GARS-3), and laboratory tests (plasma vasopressin, urine osmolality, and specific gravity). Results A significant inverse correlation was found between plasma vasopressin levels and ASD severity as measured by the GARS-3 total score (r = − 0.36). A significant negative correlation was also observed between urine specific gravity and the GARS-3 total score (r = − 0.36). Conclusion Plasma vasopressin levels may be a useful screening tool for assessing ASD symptom severity and we recommend further research to assess the potentially role of VP levels in detection of pre-symptomatic infants at risk for developing autism spectrum disorder.